Requirement of ABC transporter inhibition and Hoechst 33342 dye deprivation for the assessment of side population-defined C6 glioma stem cell metabolism using fluorescent probes. Issue 1 (December 2016) - Murota, Yoshitaka; Tabu, Kouichi; Taga, Tetsuya
Abstract Background Elucidating the precise properties of cancer stem cells (CSCs) is indispensable for the development of effective therapies against tumors, because CSCs are key drivers of tumor development, metastasis and relapse. We previously reported that the Hoechst 33342 dye-low staining side population (SP) method can enrich for CSCs in the C6 glioma cell line, and that the positively stained main population (MP) cells are non-CSCs. Presence of cancer stem-like SP cells is reported in various types of cancer. Although altered cellular energy metabolism is a hallmark of cancer, very little has been studied on the applicability of fluorescent probes for the understanding of CSC energy metabolism. Methods The metabolic status of C6 SP and MP cells are evaluated by CellROX, MitoTracker Green (MTG) and JC-1 for cellular oxidative stress, mitochondrial amount, and mitochondrial membrane potential, respectively. Results SP cells were found to exhibit significantly lower fluorescent intensities of CellROX and MTG than MP cells. However, inhibition of ATP binding cassette (ABC) transporters by verapamil enhanced the intensities of these probes in SP cells to the levels similar to those in MP cells, indicating that SP cells expel the probes outside of the cells through ABC transporters. Next, SP cells were stained with JC-1 dye which exhibits membrane potential dependent accumulation in mitochondrial matrix, followed by formation of aggregates. The mitochondrial membrane potential indicated by the aggregates of JC-1 was 5.0-fold lower in SP cells than MP cells. Inhibition of ABC transporters enhanced the fluorescent intensities of the JC-1 aggregates in both SP and MP cells, the former of which was still 2.2-fold lower than the latter. This higher JC-1 signal in MP cells was further found to be due to the Hoechst 33342 dye existing in MP cells. When SP and MP cells were recultured to deprive the intracellular Hoechst 33342 dye and then stained with JC-1 in the presence of verapamil, the intensities of JC-1 aggregates in such SP and MP cells became comparable. Conclusion Inhibiting ABC transporters and depriving Hoechst 33342 dye are required for the accurate assessment of side population-defined C6 glioma stem cell metabolism using fluorescent probes.